Agrobiodiversity and value chains - Borelli, Teresa (2025)
This keynote presentation explores how developing strong, inclusive value chains for agrobiodiversity—especially for neglected and underutilized species —can drive sustainable food systems and improve livelihoods. Drawing on lessons from the Biodiversity for Food and Nutrition (BFN) project, the CGIAR Nature-Positive Solutions (NATURE+) Initiative, and the EU-funded DIVINFOOD projects, the talk highlights successful strategies to link smallholder farmers, cooperatives, processors, schools, chefs, and consumers. It emphasizes the importance of end-to-end thinking, from seed systems and gender equity to market access and institutional demand. Through real-world examples across Africa, Asia, Latin America, and Europe, this keynote provides a compelling case for integrating agrobiodiversity into food value chains to support climate resilience, nutrition, and local economies.